Evaluasi pengelolaan limbah medis pada masa pandemi COVID-19 di RSUD Petala Bumi provinsi Riau - yyusmarni yyusmarni; Rahman Karnila; Suyanto Suyanto (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2023)
Services for COVID-19 infections have an impact on increasing the amount of infectious waste so that it burdens health care facilities. The Petala Bumi Regional General Hospital, Riau Province, is one of the hospitals that provide services to patients with suspected or confirmed Covid-19. Before the 2019 pandemic, the amount of medical solid waste generated was an average of 25 kg/day or 8,304.4 kg during 2019. In 2020 it increased by 45.07% or 12,047.7 kg/year, for 2021 it increased by 51.56% or 18,257 .5 kg/year. The results of the research on the process component show that the overall Covid-19 medical waste generated by the Petala Bumi Hospital, Riau Province in 2021 has been managed by carrying out management stages starting from reducing and sorting waste at the waste source, storing and transporting waste to B3 waste TPS. , storage of waste at TPS as well as transportation and final disposal of waste carried out by a tripartite agreement between the hospital, transporter and the processing party. The results of the analysis on the output component. The implementation of infectious medical waste management during the Covid-19 pandemic at the Petala Bumi Hospital, Riau Province as a whole has been carried out according to the existing stages.